63. Quantification of skin dose changes during Tomotherapy for head-neck cancer by dose-of-the-day recalculation. (December 2018) - Mori, M.; Branchini, M.; Broggi, S.; Dell'Oca, I.; Cattaneo, G.M.; Perna, L.; Calandrino, R.; Muzio, N.G. Di; Fiorino, C.
Abstract : Purpose: An increase of skin dose during RT for head-neck (HN) cancer due to anatomy deformation may potentially translate into an increased risk of skin toxicity, suggesting a potential benefit from planning adaptation (ART) to counteract this effect. Current study applied an original method for dose-of-the-day calculation in quantifying changes of skin dose during Tomotherapy for head and neck (HN) cancer in order to identify those patients that could benefit of ART. Methods: Planning CTs of 32 patients (SIB: 54/66 Gy, 30 fractions) were deformable registered to MVCT images taken at fraction 15 and 30 using a constrained-intensity-based algorithm. Dose-of-the-day were calculated on the deformed images; this approach was previously validated by comparing dose distributions of deformed CT and diagnostic kVCT of the same day. Superficial body layers (SL) were considered as a surrogate of skin, considering a 2 mm thickness. Skin dose variation during therapy ( Δ SL) in terms of fraction of SL receiving at least 95%–105% of the prescribed PTV dose (66 Gy) were considered. Based on the previous validation, a change ≥ + 1 cc was assessed to define patients that may benefit of ART. Results: Δ SL occurred during treatment with individually variable patterns, depending on several factors like the PTV location/dimension/shape/shrinkage. Only 3 patients experienced >1 cc change of SL95%-105% during treatment (maximum variation: 6 cc) while negative Δ SL95%-105% > 1 cc, up to 17 cc, were seen in 15/33 patients. A negative change was correlated with the presence of some overlap between PTV and SL at planning (p = 0.03). Δ SL 95% are shown for all patients in Fig. 1. Conclusions: Most patients treated with a SIB approach with Tomotherapy for HN cancer showed negative or irrelevant changes to the dose delivered to the skin. Less than 10% of patients seem to be candidate to ART to counteract any significant skin dose increase during therapy.